2021
DOI: 10.51574/jrip.v1i2.41
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Google Classroom in English Teaching and Learning Process at Senior High School Level

Abstract: The Covid-19 pandemic requires almost all human activity to move to digital media, including education services. Recently, education services must adapt to online learning methods. In response to these changes, many states, institutions, and organizations have been working on strategic plans to implement online education. The objective of this paper was to describe the usage of google classroom in the English teaching and learning process at the senior high school level. The method used in writing this paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 4 publications
3
17
0
Order By: Relevance
“…Several studies reported obstacles and limitations of GC in online learning contexts (Harjanto & Sumarni, 2019;Nursyahrina et al, 2021;Octaberlina & Muslimin, 2020;Syahputra & Isnani, 2020). The site could not be accessed without an internet network and this could be an issue in the learning contexts whose students' and teachers' internet connectivity was not very good (Atmojo & Nugroho, 2020;Octaberlina & Muslimin, 2020;Okmawati, 2020;Rosyada, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported obstacles and limitations of GC in online learning contexts (Harjanto & Sumarni, 2019;Nursyahrina et al, 2021;Octaberlina & Muslimin, 2020;Syahputra & Isnani, 2020). The site could not be accessed without an internet network and this could be an issue in the learning contexts whose students' and teachers' internet connectivity was not very good (Atmojo & Nugroho, 2020;Octaberlina & Muslimin, 2020;Okmawati, 2020;Rosyada, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The site could not be accessed without an internet network and this could be an issue in the learning contexts whose students' and teachers' internet connectivity was not very good (Atmojo & Nugroho, 2020;Octaberlina & Muslimin, 2020;Okmawati, 2020;Rosyada, 2020). Another limitation found by Nursyahrina et al (2021) was that GC was too "Googlish" in that it had various buttons only recognizable to Google users.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kahoot platform can be used to create both quizzes and games. It provides features such as quiz feature, jumble feature, discussion feature, and survey feature (A'Yun et al, 2021;Choirunnisa & Mandasari, 2021;Laili & Muflihah, 2020;Nursyahrina et al, 2021). Moreover, the quizzes or questions in Kahoot can be presented with pictures and recordings (Mu'awanah et al, 2021;Safira et al, 2021;Sofyana Abdurrachman;Shakiyya, Zulfa, 2020).…”
Section: Introductionmentioning
confidence: 99%